2020
DOI: 10.1101/2020.04.27.20073858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 Serology in Asymptomatic Healthcare Professionals: Preliminary Experience of a Tertiary Italian Academic Center

Abstract: We investigated the SARS-CoV-2 specific antibody titers in 133 asymptomatic healthcare providers working at the Department of Laboratory Medicine of our tertiary center. A commercial chemiluminescence immunoassay, validated according to the ISO15189 standard requirements, was used. All the enrolled healthcare professionals underwent, simultaneously to the blood sampling, a nasopharyngeal swab for molecular testing with quantitative reverse-transcriptase-based polymerase chain reaction (RT-PCR). An overall posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…To date, these studies have been heterogeneous in the population studied, their sampling, methodological rigour and use of a range of non-validated antibody tests with low sensitivity or specificity, or have not reported the performance characteristics of the chosen assay ( Bobrovitz et al , 2020 ). Despite these limitations, seroprevalence estimates for health-care workers have ranged from 5.2% to 24.4%, approximately twice that of the general population and substantially higher than the 4% reported here ( Garcia-Basteiro et al , 2020 ; Pollán et al , 2020 ; Steensels et al , 2020 ; TosaTo et al , 2020 ). This may reflect the standalone nature of fertility centres, i.e.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…To date, these studies have been heterogeneous in the population studied, their sampling, methodological rigour and use of a range of non-validated antibody tests with low sensitivity or specificity, or have not reported the performance characteristics of the chosen assay ( Bobrovitz et al , 2020 ). Despite these limitations, seroprevalence estimates for health-care workers have ranged from 5.2% to 24.4%, approximately twice that of the general population and substantially higher than the 4% reported here ( Garcia-Basteiro et al , 2020 ; Pollán et al , 2020 ; Steensels et al , 2020 ; TosaTo et al , 2020 ). This may reflect the standalone nature of fertility centres, i.e.…”
Section: Discussioncontrasting
confidence: 70%
“…Several large scale serological surveys of SARS-CoV-2 have been performed (Adams et al ; Bryan et al , 2020 ; Garcia-Basteiro et al , 2020 ; Pollán et al , 2020 ; Salje et al , 2020 ; Snoeck et al , 2020 ; Sood et al , 2020 ; Steensels et al , 2020 ; Stringhini et al , 2020 ; Valenti et al , 2020 ) or are ongoing ( Bobrovitz et al , 2020 ), with several including data on health-care workers ( Garcia-Basteiro et al , 2020 ; Korth et al , 2020 ; Pollán et al , 2020 ; Shields et al , 2020 ; Steensels et al , 2020 ; TosaTo et al , 2020 ). To date, these studies have been heterogeneous in the population studied, their sampling, methodological rigour and use of a range of non-validated antibody tests with low sensitivity or specificity, or have not reported the performance characteristics of the chosen assay ( Bobrovitz et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies was conducted in Europe (n=31), and then in North America (n=9), Asia (n=6), and Africa (n=3). In particular, nine studies was conducted in USA [ 14 , 15 , 24 , 26 , 27 , 29 , 32 , 34 , 40 ], eight studies in Italy [ 23 , 28 , 30 , 36 , 44 , 45 , 56 , 57 ], seven studies in United Kingdom [ 16 , 17 , 20 , 25 , 33 , 59 , 61 ], five studies in Germany [ 21 , 35 , 42 , 43 , 46 ], four studies in Spain [ 31 , 38 , 49 , 52 ], and three studies in and Japan [ 53 , 58 , 62 ], Belgium [ 18 , 19 , 22 ] and China [ 47 , 48 , 51 ]. Twenty-nine studies did not report the response rate [ [15] , [16] , [17] , 20 , 24 , [26] , [27] , [28] , [29] , [30] , [32] , [33] , [34] , 38 , [40] , [41] , [42] , [43] , 45 , 47 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…79 A study reported from Italy showed 5.25% seropositivity within the asymptomatic health care providers. 80 By contrast, another study from Italy screened health workers and observed discordant results between two immunological assays in reporting sensitivity. 81 Interestingly, a study with health care workers in Switzerland showed negative virus-specific antibodies in serum, whereas it was detected in nasal fluids and tears.…”
Section: A Hunt For Asymptomatic Casesmentioning
confidence: 97%